2009
DOI: 10.1073/pnas.0909954106
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirements of MHC and of DCs for endogenous proliferation of different T-cell subsets in vivo

Abstract: T cells transferred into severe lymphopenic hosts undergo rapid proliferation known as ''endogenous proliferation'' that are distinct from conventional homeostatic proliferation. Unlike homeostatic proliferation, cytokines, such as IL-7 are dispensable, yet TCR:MHC interaction is essential for this process to occur. However, cell types inducing the proliferation have not formally been addressed. In this study, we report that CD11c؉ conventional DCs play irreplaceable roles in inducing endogenous proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…We previously reported that naïve CD8 T-cell proliferation under lymphopenic conditions is not influenced by the lack of MHC I, and that the MHC I-independent CD8 proliferation requires MHC II (12). CD8 T cells that either are restricted to or crossrecognize MHC II have been reported previously (13,14), although the frequency of these cells is likely low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that naïve CD8 T-cell proliferation under lymphopenic conditions is not influenced by the lack of MHC I, and that the MHC I-independent CD8 proliferation requires MHC II (12). CD8 T cells that either are restricted to or crossrecognize MHC II have been reported previously (13,14), although the frequency of these cells is likely low.…”
Section: Resultsmentioning
confidence: 99%
“…Under lymphopenic settings, naïve T cells undergo endogenous proliferation (7,8) induced in part by recognition of self-peptide-MHC complexes, occurring in a MHC-restricted manner (9)(10)(11). Unlike naïve CD4 T cells that fail to proliferate in MHC II-deficient lymphopenic recipients, naïve CD8 T cells undergo substantial proliferation in MHC I-deficient lymphopenic conditions (12). This MHC I-independent proliferation is completely abolished in the absence of both MHC I and MHC II molecules, suggesting the possible involvement of a CD8 T-cell-MHC II molecule interaction in this proliferation (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphopenia driven activation results from reduced competition for resources (MHC on dendritic cells and cytokines) that occurs within lymphopenic lymph nodes, and can be blocked by reducing lymph node stroma [5] or by increasing the number of competitor T cells [1]; polyclonal naïve T cells compete with each other to bind with self-MHC/peptide complexes and cytokines for their survival and homeostatic proliferation [36]. Therefore, we further tested our conclusion that PD-1 was needed to control homeostatic activation of RTE cells by using two separate approaches to increase the competition for resources.…”
Section: Control Of Lymphopenia Driven Activation and Autoimmunity Thmentioning
confidence: 99%
“…There is evidence for several distinct forms of LIP, including a rapid or acute proliferation (also called endogenous proliferation), a slower IL-7 dependent 'homeostatic' proliferation, and a rapid expansion of CD8 central memory cells that occurs in the presence of excess IL-15. Both the slow [2e4] and rapid [5] forms of LIP demonstrate dependence on the presence of adequate lymph node stroma, particularly in the case of CD4 LIP [2e4]. In contrast, the form of LIP that leads to proliferation of central memory CD8T cells, as occurs in lymphopenic mice lacking NK cells (e.g.…”
Section: Introductionmentioning
confidence: 98%